Refleksja nad koncepcją folwarcznych korzeni polskiej kultury gospodarczej Janusza Hryniewicza - Banach , Wiesław (Człowiek i Społeczeństwo, 2020)
The main aim of the article is to examine Janusz Hryniewicz’s concept of Polish economic culture. According to the discussed author, a lot of elements present in contemporary Polish companies and organizations (economic practices) are the result of participation in an East-Central Europe economic and social system based on agriculture. Processes of long duration led to a division of the European space in the 16th century: in Western Europe we can see the development of capitalism and its institutions; in East-Central Europe, the rise of a social and economic system based on the manorial-serf economy (called new serfdom). Hryniewicz tries to show the link between rules of misconduct in the 16th century manor farm and the contemporary attitude to the job of workers and managers alike. The paper is an attempt to show the discussed concept from an anthropological and cultural studies perspective.